Mindfulness‐based parenting programmes for improving psychosocial outcomes in children from birth to age 18 and their parents - Shlonsky, A; Dennis, JA; Devine, B; Tufford, L; Barlow, J; Bjørndal, A (Wiley, 2016)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: